Religious Well-Being and Suicide Ideation in Veterans - An Exploratory Study - Kopacz, Marek S. (Pastoral psychology, 2016)
Religious well-being is a multi-faceted construct posited as a protective factor against suicidal thoughts and behaviors. This cross-sectional, exploratory study used religious practice data collected from n = 5378 U.S. military veterans to create composite measures of private and public religious practice. These composite measures were subsequently used to determine the probability of being identified with a history of suicide ideation. Data analysis was conducted using logistic regression. Veterans with a history of suicide ideation made up 10.2 % ( n = 549) of the sample. Such veterans had significantly lower mean public and private religiosity scores compared to those without ideation. Differences between these two composite measures of religiosity were associated with a higher probability of being identified with a history of suicide ideation. The present study adds to the extant literature by presenting a framework for interpreting religious well-being in the context of religious practice. Quantitative differences in engagement between private and public practices may be indicative of a decreased sense of religious well-being, conferring less protection against suicidal behavior.